Career Orientations of Students — Future Teachers at the Final Stage of University Training - Kremen, S.A.; Kremen, F.M. (Bulletin of Practical Psychology of Education, 2024)
One of the areas of studying the motivational bases of choosing and entering the teaching profession is the study of career orientations of students at different stages of professional training. The article presents the results of a study conducted with 36 fifth year undergraduate students in the Field of training 44.03.05 Pedagogical Education (double major) of Smolensk State University. The use of the diagnostic methodology "Career Anchors" by E. Schein and a questionnaire to determine socio-demographic and motivational-professional characteristics showed that the dominant career orientations of graduates correlate with both the values of social utility (service) and the motives of external utility (job stability, integration of lifestyles). Subsequent analysis showed that students who consciously chose the teaching profession and want to work in their specialty also have higher scores on the scale of professional competence. The subjects are aware of the social significance, creative nature and complexity of the teaching profession. They attach great importance to stable working and living conditions for professional development. Одним из направлений изучения мотивационных основ выбора и вхождения в педагогическую профессию является рассмотрение карьерных ориентаций студентов на разных этапах профессиональной подготовки. В статье представлены результаты исследования, проведенного с 36 студентами выпускного курса бакалавриата направления подготовки 44.03.05 Педагогическое образование (с двумя профилями) Смоленского государственного университета. Использование диагностической методики Э. Шейна «Якоря карьеры» и опросника для определения социально-демографических и мотивационно-профессиональных характеристик показало, что доминирующие карьерные ориентации выпускников соотносятся как с ценностями социальной полезности (служение), так и с мотивами внешней полезности (стабильность места работы, интеграция стилей жизни). Последующий анализ выявил, что у студентов, осознанно выбравших профессию учителя и желающих работать по специальности, более высокие показатели также по шкале профессиональной компетентности. Испытуемые осознают социальную значимость, творческий характер и сложность учительской профессии. Важное значение для профессионального развития они придают стабильным условиям труда и жизни.